Race and militarized police violence in Brazil - Pinto, Simone Rodrigues (Police and state crime in the Americas, 2024)
Current official data indicate that the police are the main perpetrators of shoot deaths and injuries of Blacks in Brazil. The Brazilian Security Forum, the main source of public security data in the country, shows that of the 6,416 Brazilians killed by police intervention in 2020, 78.9% were Black. Racism is masked by distorted narratives in official police records and media accounts of local events, which are then welcomed by a society permeated by historically structured Negrophobia. This text seeks to reflect on the performance of the Brazilian military police and the racist bias of their interventions, especially on the outskirts of large cities.